Nitrogen availability and biomass yield of Ricinus communis L. fertilized with biosolids - Maciel Torres, Sandra Patricia; Figueroa Viramontes, Uriel; Jacobo-Salcedo, Maria Rosario; Trejo Calzada, Ricardo; Pedroza Sandoval, Aurelio; Encerrado Alva, Ruben Carlos (Revista Mexicana de Ciencias Agrícolas, 2020)
A criterion to estimate the application dose of biosolids in agricultural soils is the available nitrogen and the requirement of the crop. The objective of the study was to determine the nitrogen availability of two biosolids generated from different treatment systems and its effect on the oil yield from Ricinus communis L. seed. The treatments consisted of three sources of nitrogen (N) and three doses, in addition to a control without N. The sources of N were: ammonium sulfate (SA), biosolids from oxidation lagoons (BLO) and biosolids from activated sludge (BLA). The SA was considered as a commercial witness. The doses of N were 0, 3.79, 5.65 and 7.52 g pot-1, which correspond to 67%, 100% and 133% of the N requirement of the crop (RNC), respectively. The greenhouse experiment was established under a randomized block experimental design with four replications, where the experimental unit was one plant per pot. Nitrogen availability was estimated using the fertilizer equivalency method (EF). The dry matter (DM) was statistically similar between the treatments, being different from the control (p< 0.05). The DM and N extraction showed a quadratic response as a function of the applied N doses. The availability of N was 40.4 and 34.8% for the BLA and BLO, respectively.